2011
DOI: 10.1371/journal.pone.0028038
|View full text |Cite
|
Sign up to set email alerts
|

Health Behaviors, Care Needs and Attitudes towards Self-Prescription: A Cross-Sectional Survey among Dutch Medical Students

Abstract: PurposeThere is a growing awareness of the potent ways in which the wellbeing of physicians impacts the health of their patients. The purpose of this study was to investigate the health behaviors, care needs and attitudes towards self-prescription of Dutch medical students, and any differences between junior preclinical and senior clinically active students.MethodsAll students (n = 2695) of a major Dutch medical school were invited for an online survey. Physical activity, eating habits, alcohol consumption, sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
28
0
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 40 publications
3
28
0
11
Order By: Relevance
“…A literatura tem mostrado que há uma consciência crescente de que o bem-estar dos médicos e seus hábitos afetam a saúde de seus pacientes, o que também incluí a atividade física 16,17,[26][27][28] . Um estudo prospectivo 16 com uma amostra representativa (N = 2.316) dos estudantes de medicina dos EUA de 16 universidades evidenciou que os estudantes de medicina que cumpriram ou aderiram às recomendações de atividade física ao longo dos quatro anos do estudo demonstraram melhor saúde mental, maior taxa de prescrição da atividade física e maior influência dessas prescrições em relação aos seus pacientes.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…A literatura tem mostrado que há uma consciência crescente de que o bem-estar dos médicos e seus hábitos afetam a saúde de seus pacientes, o que também incluí a atividade física 16,17,[26][27][28] . Um estudo prospectivo 16 com uma amostra representativa (N = 2.316) dos estudantes de medicina dos EUA de 16 universidades evidenciou que os estudantes de medicina que cumpriram ou aderiram às recomendações de atividade física ao longo dos quatro anos do estudo demonstraram melhor saúde mental, maior taxa de prescrição da atividade física e maior influência dessas prescrições em relação aos seus pacientes.…”
Section: Discussionunclassified
“…Van der Veer et al,. 28 baseados em uma amostra de 962 estudantes de medicina holandeses, verificaram a prevalência de comportamentos não saudáveis, sendo que o estudo concluíu que as faculdades de medicina necessitam abordar formas de promover comportamentos saudáveis tanto para o benefício de seus alunos, como dos médicos e dos pacientes.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…HCPs played an important role in smoking cessation campaigns. There are some remarkable examples from the United Kingdom and Sweden [17,18]. In UK, researchers collected information from hospital staff and found that the smoking rate among HCPs was lower (overall 7%; doctors 2.6%; medical students 3.8%; nurses 8.7%; allied health professionals 10.9%) than the general population (24%) [18].…”
mentioning
confidence: 99%
“…There are some remarkable examples from the United Kingdom and Sweden [17,18]. In UK, researchers collected information from hospital staff and found that the smoking rate among HCPs was lower (overall 7%; doctors 2.6%; medical students 3.8%; nurses 8.7%; allied health professionals 10.9%) than the general population (24%) [18]. Similar findings were revealed by study from Sweden that shows a lower (6%) prevalence of smoking among HCPs than the general population (19%) [17].…”
mentioning
confidence: 99%